EFEKTIFITAS PENEMPATAN TENAGA KERJA LOKAL DI KABUPATEN BENGKALIS STUDI KASUS DI KECAMATAN MANDAU - Vievin Noer Cynthia; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Mandau Subdistrict has a great potential in natural resources about 450 thousand barrels of oil produced every day and accounts for about 60% of crude oil production Indonesia. Dozens of companies operating in the Mandau Subdistrict but many local people who became unemployed because the energy imported from outside the Bengkalis District and has high position in the company that recruited. The reason companies do not use local employment as having skills and skills in the work. To protect the local employment, the government of Bengkalis District passed a local regulations No. 04 Year 2004 about Local employment.The concept of the theory that the researchers use a effectiveness theory proposed by Gibson which consists of clarity of objectives to be achieved, clarity of the strategy to achieve the goal, the process of analysis and policy formulation steady, careful planning, proper programming, the availability of infrastructure work, monitoring and control systems that are educational. This study uses qualitative research methods to study descriptive data. In the data collection, the author uses the technique of interview, observation and documentation. By using key informants as a source of information and triangulation technique as a data source in testing validity.The result of this study indicate that the local employment yet effective. It can be seen from the results that the local employment has not reached the limit on the set of local regulations No. 04 Year 2004. This is caused by the training program needs to be adjusted again to the type of labor market needs, the resources of the government apparatus that is less, information jobs that do not exist so as to make the job seekers do not get a job lead to increased unemployment in the Mandau District.Keywords : Effectiveness, Local regulations, Local employment